Primary mediastinal tumors and cysts: diagnosis and surgical treatment - Mendoza Euwing, Carlos (1989)
Invasive and non invasive methods of diagnosis and the results of surgical treatment in relation to a series of 32 cases operated on benign primary tumors of the mediastinum area within the last 24 years until 1988 are revised. The age ranged between 10 and 65 years with a 65.0% predominance of females. According to the histological diagnosis and incidence, the tumors were 10 cases, 31.2% of thymic origin; seven cases, 21.8% teratodermoid cysts; two cases, 6.3% of thyroid; two cases, 6.3% celomic cysts; two cases, 6.3% bronchogenic systs and two cases, 6.3%, of benign primary cardiac mixoma. Malignant changes were found in two cases, 6.3%. Mortality rate was 6.3%, two cases, in the inmediate posoperative. In one case of teratoma, after three years of surgical removal there was recidive. A favorable evolution and recovery was seen in 91.0% of the cases. We propose to include mixomas in the classification of tumors and cysts of the mediastinum, because in our study we found them to be intracardiac, primary of the mediastinum, benign and wholly removable by the surgical technic of extracorporal circulation, temporally cardiac stop, which was done with siccess and recovery in our patients (An Fac Med UNMSM II Epoca 1989; 1 (1-2): 55-60).